Pengaruh Model Pembelajaran Kooperatif Tipe Example Non Example Berbantuan Kertas Duplek Terhadap Peningkatan Pemahaman Konsep Bangun Ruang - Nur Kummala; Pujilestari Pujilestari (Lembaga Penelitian dan Pendidikan Mandala, 2020)
The purpose of this study was to determine whether or not there is an effect of the example non example cooperative learning model assisted by duplex paper to increase understanding of the concept of building. This research design used Postest Only Control Design. The research sample was 70 students who were selected using purposive sampling technique. The experimental class uses the example non example learning model, while the control class uses a conventional learning model. Based on the result of the research from the normality and homogeneity test with the assistance of spss version 16 from the two data groups of the sample, both data were normal and homogeneous, so that the hypothesis testing used the t-test assisted by spss version 16. From the data results obtained a value (2-sig. Tailed. ) < 0.05, namely 0.000 < 0.05 at the 5% significance level, then Ha is accepted and H0 is rejected, which means that there is an effect of the example non example type of learning model on students' conceptual understanding. This shows that the use of the example non example type of learning model for students' understanding of concepts gave better result than using the conventional learning model.